Liquid crystal alignment treating agent, liquid crystal alignment film and liquid crystal display element

By using liquid crystal alignment treatment agents of specific compounds and polymers in liquid crystal display elements, the adhesion between the liquid crystal alignment film and the metal electrode is enhanced, and the bubble generation and peeling of the liquid crystal display elements is solved at high temperature and high humidity, achieving high quality Stable and durable LCD display components.

CN113474724BActive Publication Date: 2024-12-17NISSAN CHEM CORP
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202080016064.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2019-03-08
Filing Date
2020-03-06
Publication Date
2024-12-17
Estimated Expiration
2040-03-06

AI Technical Summary

Technical Problem

Under high temperature and high humidity conditions, liquid crystal display elements are prone to water infiltration, bubble generation and peeling problems between the sealant and the liquid crystal orientation film, resulting in uneven display and component failure. Although the addition of alkoxysilane compounds in the prior art can improve Adhesion but poor storage stability.

Method used

The liquid crystal alignment treatment agent containing specific compounds and specific polymers is used to enhance adhesion through the chemical reaction between the phosphate-based compound and the metal electrode, and chemical bonding is carried out under ultraviolet rays to improve the adhesion between the liquid crystal alignment film and the sealant.

Benefits of technology

It significantly improves the storage stability of liquid crystal display components and the resistance under high temperature and high humidity, prevents bubble generation and component peeling, and is suitable for smartphones and other devices.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN113474724B_ABST
    Figure CN113474724B_ABST
Patent Text Reader

Abstract

The object of the present invention is to provide a liquid crystal alignment agent having excellent storage stability, high adhesion (also called tightness) between substrates of a liquid crystal display element, and a liquid crystal alignment film that can suppress the generation of bubbles in the liquid crystal display element and the peeling of the element even when exposed to a high temperature and high humidity environment for a long time. The liquid crystal alignment agent contains the following components (A) and (B), component (A): a compound of the following formula [1], component (B): a polymer having at least one structure selected from the following formulas [2-a] to [2-i], and the definitions of the symbols in the formulas are as described in the specification. #imgabs0#
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a liquid crystal aligning agent for producing a liquid crystal display element, a liquid crystal aligning film obtained from the liquid crystal aligning agent, and a liquid crystal display element using the liquid crystal aligning film. Background Art

[0002] Films made of organic materials such as polymer materials have attracted attention for their ease of formation and insulation performance, and are widely used as interlayer insulating films, protective films, etc. in electronic devices. Among them, organic films made of polyimide are used as liquid crystal alignment films in liquid crystal display elements that are well-known as display devices.

[0003] A liquid crystal alignment film is used for the purpose of controlling the alignment state of liquid crystals. However, as liquid crystal display elements become more precise, it is required to suppress a decrease in contrast of the liquid crystal display elements and display defects caused by long-term use.

[0004] In contrast, in a liquid crystal alignment film using polyimide, as a method for improving the orientation of the liquid crystal and preventing display defects from occurring in the periphery of the liquid crystal display screen, a liquid crystal alignment film using a liquid crystal alignment treatment agent to which an alkoxysilane compound is added has been proposed (for example, see Patent Document 1 or Patent Document 2).

[0005] Prior art literature

[0006] Patent Literature

[0007] Patent Document 1: Japanese Patent Application Laid-Open No. 61-171762

[0008] Patent Document 2: Japanese Patent Application Laid-Open No. 11-119226 Summary of the invention

[0009] Problems to be solved by the invention

[0010] In recent years, liquid crystal display elements have been used for mobile applications such as smart phones and portable phones. In these applications, in order to ensure as many display surfaces as possible, it is necessary to set the width of the sealant between the substrates for bonding the liquid crystal display element to be narrower than before. Moreover, according to the above reasons, it is also required to set the drawing position of the sealant to a position that is connected to the end of the liquid crystal alignment film with weak adhesion of the sealant, or to the upper part of the liquid crystal alignment film. Therefore, in recent years, compared with the past, it has become a situation where the adhesion between the substrates of the liquid crystal display element is weak. Moreover, in such a case, due to the use under high temperature and high humidity conditions, water is easily mixed between the sealant and the liquid crystal alignment film, which is easy to cause uneven display near the frame of the liquid crystal display element, bubbles are generated in the element, and then the peeling of the element is caused.

[0011] In view of this problem, as a method for improving the adhesion between the liquid crystal alignment film and the sealant, there is a method of adding an alkoxysilane compound to the liquid crystal alignment treating agent. However, when an alkoxysilane compound is added to the liquid crystal alignment treating agent, although the adhesion between the sealant and the liquid crystal alignment film can be improved, during the storage period of the liquid crystal alignment treating agent, the condensation reaction of the alkoxy group in the alkoxy compound will proceed, and there is a problem that the storage stability of the liquid crystal alignment treating agent deteriorates, such as the viscosity of the liquid crystal alignment treating agent increases and a gel is generated.

[0012] According to the above aspects, the object of the present invention is to provide a liquid crystal aligning agent having excellent storage stability, high adhesion (also referred to as close adhesion) between substrates of a liquid crystal display element, and a liquid crystal aligning film that can suppress the generation of bubbles in the liquid crystal display element and the peeling of the element even when exposed to a high temperature and high humidity environment for a long time. In addition, it is also intended to provide a liquid crystal display element having the above-mentioned liquid crystal aligning film and a liquid crystal aligning agent that can provide the above-mentioned liquid crystal aligning film.

[0013] Solutions for solving problems

[0014] The present inventors have conducted intensive studies to achieve the above-mentioned object, and as a result, have completed the present invention having the following gist.

[0015] That is, it is a liquid-crystal aligning agent containing the following component (A) and component (B).

[0016] Component (A): a compound of the following formula [1] (also referred to as a specific compound).

[0017] Component (B): A polymer (also referred to as a specific polymer) having at least one structure (also referred to as a specific structure) selected from the following formulas [2-a] to [2-i].

[0018]

[0019] T 1 represents the following formula [1-a] or formula [1-b], T 2 represents an alkylene group having 2 to 24 carbon atoms, wherein the alkylene group does not have any carbon atoms. 1 Any -CH adjacent to O 2 - optionally with -O-, -CO-, -COO-, -OCO-, -CONH-, -NHCO-, -NH- or -CON(CH 3 )-substituted, Tm represents an integer of 1 to 2, and Tn represents an integer of 1 to 2, wherein Tm+Tn is 3.

[0020]

[0021] XA It represents a hydrogen atom or a benzene ring.

[0022] Effects of the Invention

[0023] The liquid crystal aligning agent of the present invention is excellent in storage stability, and even if a liquid crystal display element using the liquid crystal aligning agent is exposed to a severe environment of high temperature and high humidity for a long time, generation of bubbles in the liquid crystal display element and peeling of the element can be suppressed.

[0024] The mechanism of why a liquid crystal display element having the above-mentioned excellent characteristics is obtained according to the present invention is not necessarily clear, but can be roughly estimated as follows.

[0025] Since the specific compound has a phosphate group that strongly interacts with metals, the adhesion between the liquid crystal alignment film obtained by the liquid crystal alignment agent containing the specific compound and a metal electrode such as an ITO electrode is enhanced. 1 The structure of can react with the specific structure in the specific polymer under the action of ultraviolet rays and heat. Therefore, the specific compound that can enhance the adhesion with the metal electrode is chemically bonded to the specific polymer that becomes the base of the liquid crystal alignment film. It can be considered that compared with the previous method of adding a low molecular compound that can enhance the adhesion with the metal electrode to the liquid crystal alignment agent, the adhesion between the liquid crystal alignment film and the metal electrode can be made stronger.

[0026] In addition, since the specific structure in the specific polymer reacts under the action of ultraviolet rays, the specific structure in the specific polymer will react with the reactive groups of the polymerizable compound in the sealant during the hardening treatment of the sealant when making a liquid crystal display element. Specifically, under the irradiation of ultraviolet rays, the adhesion between the liquid crystal orientation film and the sealant becomes strong.

[0027] Therefore, after the liquid crystal alignment film is formed by the liquid crystal display element using the liquid crystal alignment agent containing the specific compound and the specific polymer, the adhesion between the liquid crystal alignment film and the metal electrode, and between the liquid crystal alignment film and the sealant is enhanced, and even if it is exposed to a high temperature and high humidity environment for a long time, the generation of bubbles in the liquid crystal display element and the peeling of the element can be suppressed. Therefore, the liquid crystal display element of the present invention can be used in liquid crystal display elements of smart phones, portable phones, etc. DETAILED DESCRIPTION

[0028] <Specified compounds>

[0029] The specific compound is the compound of the above formula [1].

[0030] In formula [1], T 1 , T 2 , Tm and Tn are as defined above, wherein each is preferably as follows.

[0031] T 1 Preferred is the above-mentioned formula [1-a] or formula [1-b].

[0032] T 2 It is preferably an alkylene group having 2 to 12 carbon atoms and not 1 Any -CH adjacent to O 2 - is optionally substituted with -O-, -COO- or -OCO-.

[0033] Tm is preferably an integer of 1 to 2. Tn is preferably an integer of 1 to 2. In this case, Tm+Tn is 3.

[0034] Specific examples of the specific compound include compounds of the following formula [1a-1] to [1a-3], and these are preferably used.

[0035]

[0036] T a represents the above formula [1-a] or formula [1-b], T b Each of them represents an alkylene group having 2 to 18 carbon atoms, T c Indicates -COO- or -OCO-, T d represents an alkylene group having 2 to 12 carbon atoms, p1 represents an integer of 1 to 2, p2 represents an integer of 1 to 2, wherein p1+p2 is 3, and p3 represents an integer of 2 to 8.

[0037] More specifically, Phosmer M, Phosmer PE, Phosmer PP (all manufactured by DAP Co., Ltd.), Light Acrylate P-1A(N), Light Ester P-1M (all manufactured by Kyoeisha Chemical Co., Ltd.), KAYAMER PM-2, and KAYAMER PM-21 (all manufactured by Nippon Kayaku Co., Ltd.), and these are preferably used.

[0038] From the aspect of the adhesion between the liquid crystal alignment film and the electrode of the liquid crystal display element, the specific compound is preferably used in a ratio of 0.01 to 20 parts by mass relative to 100 parts by mass of all polymers in the liquid crystal alignment agent. More preferably, it is 0.05 to 10 parts by mass. Particularly preferably, it is 0.1 to 10 parts by mass. In addition, according to each characteristic, the specific compound can be used alone or in combination of two or more.

[0039] <Specific structure / Specific polymer>

[0040] The specific structure is at least one structure selected from the group consisting of the above formula [2-a] to formula [2-i].

[0041] Among them, the above-mentioned formula [2-a] to formula [2-c], formula [2-e], formula [2-h] or formula [2-i] are preferred. Formula [2-a], formula [2-b], formula [2-h] or formula [2-i] are more preferred. The specific polymer having a specific structure is not particularly limited, but is preferably at least one polymer selected from acrylic polymers, methacrylic polymers, novolac resins, polyhydroxystyrene, polyimide precursors, polyimide, polyamide, polyester, cellulose or polysiloxane. Polyimide precursors, polyimide or polysiloxane are more preferred.

[0042] The specific structure is preferably a form of a repeating unit contained in a polymer. Relative to all repeating units constituting the polymer, the repeating unit containing the specific structure is preferably 10 to 70 mol%. More preferably, 20 to 60 mol%. In addition, according to each characteristic, the specific polymer with a specific structure can be used one or more than two.

[0043] When a polyimide precursor or polyimide (also collectively referred to as a polyimide-based polymer) is used as the specific polymer, a polyimide precursor or polyimide obtained by reacting a diamine component with a tetracarboxylic acid component is preferred. The polyimide-based polymer may be used alone or in combination of two or more depending on the properties.

[0044] The polyimide precursor has a structure of, for example, the following formula [A].

[0045]

[0046] R 1 represents a tetravalent organic group. 2 Represents a divalent organic group. 1 and A 2 Each of them represents a hydrogen atom or an alkyl group having 1 to 8 carbon atoms. 3 and A 4 Each of them represents a hydrogen atom, an alkyl group having 1 to 5 carbon atoms, or an acetyl group. n represents a positive integer.

[0047] The diamine component is a diamine having two primary or secondary amino groups in the molecule. The tetracarboxylic acid component includes a tetracarboxylic acid compound, a tetracarboxylic dianhydride, a dihalogenated tetracarboxylic acid compound, a tetracarboxylic acid dialkyl ester compound, or a dihalogenated tetracarboxylic acid dialkyl ester compound.

[0048] The polyimide polymer is preferably a polyamic acid having a repeating unit structure of the following formula [D] or a polyimide obtained by imidizing the polyamic acid because it can be easily obtained by using tetracarboxylic dianhydride of the following formula [B] and diamine of the following formula [C] as raw materials.

[0049]

[0050] R 1 and R 2 and R defined in formula [A] 1 and R 2 same.

[0051]

[0052] R 1 and R 2 and R defined in formula [A] 1 and R 2 same.

[0053] In addition, A in formula [A] can also be introduced into the polymer of formula [D] obtained above by a conventional synthesis method. 1 and A 2 an alkyl group having 1 to 8 carbon atoms, and A in the formula [A] 3 and A 4 An alkyl group having 1 to 5 carbon atoms or an acetyl group.

[0054] As a method for introducing a specific structure into a polyimide-based polymer, it is preferable to use a diamine having a specific structure as part of the raw material. In particular, it is preferable to use a diamine having a structure of the following formula [2] (also referred to as a specific diamine).

[0055]

[0056] X 1 Indicates a single bond, -O-, -NH-, -N(CH 3 )-、-CH 2 O-, -CONH-, -NHCO-, -CON(CH 3 )-、-N(CH 3 )CO-, -COO- or -OCO-. Among them, a single bond, -O-, -CH 2 O-, -CONH-, -COO- or -OCO-. More preferably, it is a single bond, -O-, -CH 2 O-or-COO-.

[0057] X 2It represents a single bond, an alkylene group having 1 to 18 carbon atoms, or an organic group having 6 to 24 carbon atoms having a cyclic group selected from a benzene ring, a cyclohexane ring, and a heterocyclic ring, and any hydrogen atom on these cyclic groups is optionally substituted with an alkyl group having 1 to 3 carbon atoms, an alkoxy group having 1 to 3 carbon atoms, a fluorinated alkyl group having 1 to 3 carbon atoms, a fluorinated alkoxy group having 1 to 3 carbon atoms, or a fluorine atom. Among them, a single bond, an alkylene group having 1 to 12 carbon atoms, a benzene ring, or a cyclohexane ring is preferred. A single bond or an alkylene group having 1 to 12 carbon atoms is more preferred.

[0058] X 3 Indicates a single bond, -O-, -NH-, -N(CH 3 )-、-CH 2 O-, -CONH-, -NHCO-, -CON(CH 3 )-、-N(CH 3 )CO-, -COO- or -OCO-. Among them, a single bond, -O-, -COO- or -OCO- is preferred. A single bond or -OCO- is more preferred.

[0059] X 4 It represents any one of the above formulas [2-a] to [2-i]. Among them, formulas [2-a] to [2-e], [2-h] or [2-i] are preferred. Formulas [2-a], [2-b], [2-d], [2-e] or [2-i] are more preferred. Formulas [2-a], [2-b] or [2-i] are particularly preferred.

[0060] Xm represents an integer of 1 to 4. Among them, 1 or 2 is preferred.

[0061] As the specific diamine, it is preferable to use a diamine of the following formula [2a].

[0062]

[0063] In formula [2a], X represents the above formula [2]. 1 ~X 4 The details of and Xm, and the preferred combination are shown in the above formula [2].

[0064] Xn represents an integer of 1 to 4. Among them, 1 is preferred.

[0065] As more specific specific diamine, the following formula [2a-1] to formula [2a-12] are mentioned, and these are preferably used.

[0066]

[0067] n1 represents an integer from 1 to 12 respectively.

[0068]

[0069] n2 represents an integer of 0 to 12. n3 represents an integer of 2 to 12.

[0070] Among them, preferred are formula [2a-1], formula [2a-2], formula [2a-5] to formula [2a-7], formula [2a-11], or formula [2a-12]. More preferred are formula [2a-5] to formula [2a-7], formula [2a-11], or formula [2a-12].

[0071] From the viewpoint of adhesion between the liquid crystal alignment film of the liquid crystal display element and the sealant, the specific diamine is preferably used at a ratio of 10 to 70 mol % relative to all diamine components, and more preferably 20 to 60 mol %. In addition, the specific diamine may be used alone or in combination of two or more depending on the characteristics.

[0072] As a diamine component for preparing a polyimide-based polymer, a diamine other than a specific diamine (also referred to as other diamines) may also be included. Specifically, diamine compounds of formula [3a-1] to [3a-5] described on pages 34 to 38 of International Publication WO2016 / 076412 (published on May 19, 2016), other diamine compounds described on pages 39 to 42 of the publication, and diamine compounds of formula [DA1] to [DA15] described on pages 42 to 44 of the publication can be listed. These diamine components can be used alone or in combination of two or more, depending on the properties.

[0073] As the tetracarboxylic acid component for producing the polyimide polymer, it is preferred to use tetracarboxylic dianhydride of the following formula [3], tetracarboxylic acid which is a tetracarboxylic acid derivative thereof, a dihalogenated tetracarboxylic acid compound, a tetracarboxylic acid dialkyl ester compound or a dihalogenated tetracarboxylic acid dialkyl ester compound (these are collectively referred to as specific tetracarboxylic acid components).

[0074]

[0075] Z represents any one of the following formulas [3a] to

[31] .

[0076]

[0077] Z A ~Z D Z represents a hydrogen atom, a methyl group, a chlorine atom or a benzene ring. E and Z F represent a hydrogen atom or a methyl group, respectively.

[0078] Z in formula [3] is preferably formula [3a], formula [3c], formula [3d], formula [3e], formula [3f], formula [3g], formula [3k] or formula [3l]. More preferably, it is formula [3a], formula [3e], formula [3f], formula [3g], formula [3k] or formula [3l]. Particularly preferably, it is formula [3a], formula [3e], formula [3f], formula [3g] or formula [3l].

[0079] The specific tetracarboxylic acid component is preferably used in an amount of 1 mol% or more relative to all tetracarboxylic acid components. It is more preferably 5 mol% or more. It is particularly preferably 10 mol% or more. It is most preferably 10 to 90 mol%.

[0080] The polyimide polymer may use other tetracarboxylic acid components other than the specific tetracarboxylic acid component. Examples of other tetracarboxylic acid components include tetracarboxylic acid compounds, tetracarboxylic dianhydrides, dihalogenated dicarboxylic acid compounds, dialkyl dicarboxylate compounds, and dialkyl dihalide compounds shown below.

[0081] Specifically, other tetracarboxylic acid components described on pages 34 to 35 of International Publication WO2015 / 012368 (published on January 29, 2015) are mentioned.

[0082] The specific tetracarboxylic acid component and other tetracarboxylic acid components may be used alone or in combination of two or more thereof depending on the respective properties.

[0083] The method for synthesizing the polyimide polymer is not particularly limited. Generally, it can be obtained by reacting a diamine component and a tetracarboxylic acid component. Specifically, the method described in pages 46 to 50 of International Publication WO2016 / 076412 (published on May 19, 2016) can be cited.

[0084] The reaction of a diamine component and a tetracarboxylic acid component is usually performed in a solvent containing a diamine component and a tetracarboxylic acid component. As a solvent used at this time, it will not be specifically limited as long as the produced|generated polyimide precursor is melt|dissolved.

[0085] Specifically, examples thereof include N-methyl-2-pyrrolidone, N-ethyl-2-pyrrolidone, γ-butyrolactone, N,N-dimethylformamide, N,N-dimethylacetamide, dimethyl sulfoxide, 1,3-dimethyl-2-imidazolidinone, etc. In addition, when the polyimide precursor has high solvent solubility, methyl ethyl ketone, cyclohexanone, cyclopentanone, 4-hydroxy-4-methyl-2-pentanone, or solvents of the following formulas [D1] to [D3] can be used.

[0086]

[0087] D 1 and D 2It represents an alkyl group having 1 to 3 carbon atoms. 3 It represents an alkyl group having 1 to 4 carbon atoms.

[0088] In addition, they can be used alone or in combination. Moreover, even if it is a solvent that does not dissolve the polyimide precursor, it can be mixed with the solvent in a range where the generated polyimide precursor does not precipitate. In addition, the moisture in the organic solvent hinders the polymerization reaction and becomes the cause of hydrolysis of the generated polyimide precursor, so the organic solvent is preferably a dehydrated organic solvent.

[0089] In the polymerization reaction of the polyimide precursor, the total number of moles of the tetracarboxylic acid component when the total number of moles of the diamine component is set to 1.0 is preferably 0.8 to 1.2.

[0090] Polyimide is obtained by ring-closing a polyimide precursor. In the polyimide, the ring-closing rate of the amic acid group (also referred to as the imidization rate) does not necessarily have to be 100%, and can be arbitrarily adjusted according to the use and purpose. Among them, from the perspective of the solubility of the polyimide polymer in the solvent, it is preferably 30 to 80%. More preferably, it is 40 to 70%.

[0091] The molecular weight of the polyimide polymer is preferably 5,000 to 1,000,000, more preferably 10,000 to 150,000, based on the weight average molecular weight measured by GPC (Gel Permeation Chromatography) method, in consideration of the strength of the resulting liquid crystal alignment film, workability during formation of the liquid crystal alignment film, and coating properties.

[0092] When polysiloxane (also referred to as polysiloxane-based polymer) is used as the specific polymer, it is preferable to use a polysiloxane obtained by polycondensing an alkoxysilane of the following formula [A1] or a polysiloxane obtained by polycondensing an alkoxysilane of the formula [A1] and an alkoxysilane of the following formula [A2].

[0093] Alkoxysilane of formula [A1].

[0094] (A 1 ) m Si(A 2 ) n (OA 3 ) p [A1]

[0095] A 1It represents an organic group having 2 to 12 carbon atoms and having at least one structure selected from the above formulas [2-a] to [2-i]. Among them, preferably, it is formula [2-a] to [2-e], formula [2-h] or formula [2-i]. More preferably, it is formula [2-a], formula [2-b], formula [2-d], formula [2-e] or formula [2-i]. Especially preferably, it is formula [2-a] or formula [2-b].

[0096] A 2 It represents a hydrogen atom or an alkyl group having 1 to 5 carbon atoms. Among them, a hydrogen atom or an alkyl group having 1 to 3 carbon atoms is preferred.

[0097] A 3 It represents an alkyl group having 1 to 5 carbon atoms. Among them, an alkyl group having 1 to 3 carbon atoms is preferred.

[0098] m represents an integer of 1 or 2. Among them, 1 is preferred.

[0099] n represents an integer from 0 to 2.

[0100] p represents an integer of 0 to 3. Among them, 1 to 3 are preferred, and 2 or 3 is more preferred.

[0101] m+n+p is 4.

[0102] Specific examples of the alkoxysilane of formula [A1] are listed below.

[0103] For example, allyltriethoxysilane, allyltrimethoxysilane, diethoxymethylvinylsilane, dimethoxymethylvinylsilane, triethoxyvinylsilane, vinyltrimethoxysilane, vinyltri(2-methoxyethoxy)silane, 3-(triethoxysilyl)propyl methacrylate, 3-(trimethoxysilyl)propyl acrylate or 3-(trimethoxysilyl)propyl methacrylate are preferably used.

[0104] In addition, the alkoxysilane of formula [A1] may be used alone or in combination of two or more, depending on the properties.

[0105] Alkoxysilane of formula [A2].

[0106] (B 1 ) n Si(OB 2 ) 4-n [A2]

[0107] B 1 It represents a hydrogen atom or an alkyl group having 1 to 5 carbon atoms. Among them, a hydrogen atom or an alkyl group having 1 to 3 carbon atoms is preferred.

[0108] B 2It represents an alkyl group having 1 to 5 carbon atoms. Among them, an alkyl group having 1 to 3 carbon atoms is preferred.

[0109] n represents an integer of 0 to 3.

[0110] Specific examples of the alkoxysilane of the formula [A2] include specific examples of the alkoxysilane of the formula [2c] described on pages 24 to 25 of International Publication WO2015 / 008846 (published on January 22, 2015).

[0111] In the formula [A2], examples of the alkoxysilane in which n is 0 include tetramethoxysilane, tetraethoxysilane, tetrapropoxysilane, and tetrabutoxysilane. As the alkoxysilane of the formula [A2], these alkoxysilanes are preferably used.

[0112] The alkoxysilane of the formula [A2] may be used alone or in combination of two or more, depending on the properties.

[0113] Among them, from the aspect of the reactivity of polycondensation and the solubility of polysiloxane-based polymers in solvents, it is preferred to polycondense a plurality of alkoxysilanes to obtain polysiloxanes. That is, it is preferred to use polysiloxanes obtained by polycondensing the two alkoxysilanes of formula [A1] and formula [A2]. At this time, among all alkoxysilanes, the use ratio of the alkoxysilane of formula [A1] is preferably 1 to 70 mol%. Among them, preferably 1 to 50 mol%. More preferably 1 to 30 mol%. In addition, among all alkoxysilanes, the use ratio of the alkoxysilane of formula [A2] is preferably 30 to 99 mol%. Among them, preferably 50 to 99 mol%. More preferably 70 to 99 mol%.

[0114] The method for polycondensing the polysiloxane polymer is not particularly limited, and specific examples thereof include the method described in pages 26 to 29 of International Publication WO2015 / 008846 (published on January 22, 2015).

[0115] When using a plurality of alkoxysilanes of formula [A1] and formula [A2] in the polycondensation reaction for producing the polysiloxane polymer, the plurality of alkoxysilanes may be reacted using a mixture of the plurality of alkoxysilanes mixed in advance, or may be reacted while sequentially adding the plurality of alkoxysilanes.

[0116] In the present invention, the polysiloxane polymer solution obtained by the above method may be used as a specific polymer as it is, or the polysiloxane polymer solution obtained by the above method may be concentrated, diluted by adding a solvent, or replaced with another solvent and used as a specific polymer as needed.

[0117] The polysiloxane polymers may be used alone or in combination of two or more depending on their properties.

[0118] The solvent used for dilution (also referred to as an additional solvent) may also be the solvent used for the polycondensation reaction or other solvents. The additional solvent is not particularly limited as long as the polysiloxane polymer is uniformly dissolved therein, and one or more solvents may be selected arbitrarily. As such an additional solvent, in addition to the solvent used for the polycondensation reaction, ketone solvents such as acetone, methyl ethyl ketone, methyl isobutyl ketone, etc.; ester solvents such as methyl acetate, ethyl acetate, ethyl lactate, etc. may also be listed.

[0119] Furthermore, when a polysiloxane polymer and a polymer other than the polysiloxane polymer are used as the specific polymer, it is preferred that alcohol generated during the polycondensation reaction of the polysiloxane polymer be distilled off under normal pressure or reduced pressure before mixing the polymer other than the polysiloxane polymer with the polysiloxane polymer.

[0120] <Liquid crystal alignment agent>

[0121] The liquid crystal aligning agent contains a specific compound and a specific polymer, and is preferably a solution for forming a liquid crystal aligning film, and is a solution containing a specific compound, a specific polymer, and a solvent. In this case, two or more specific compounds and specific polymers can be used respectively.

[0122] The content of the polymer component in the liquid crystal aligning agent of the present invention can be appropriately changed according to the thickness of the liquid crystal aligning film to be formed, but is preferably 1% by weight or more from the perspective of forming a uniform and defect-free liquid crystal aligning film, and is preferably 10% by weight or less from the perspective of the storage stability of the solution. Among them, 2 to 8% by weight is preferred, and 3 to 7% by weight is particularly preferred.

[0123] The content of the solvent in the liquid crystal aligning agent can be appropriately selected from the viewpoint of the coating method of the liquid crystal aligning agent and the target film thickness. Among them, from the viewpoint of forming a uniform liquid crystal aligning film by coating, the content of the solvent in the liquid crystal aligning agent is preferably 50 to 99.9% by mass. Among them, preferably 60 to 99% by mass. More preferably 65 to 99% by mass.

[0124] The solvent used for the liquid-crystal aligning agent will not be particularly limited as long as it is a solvent which dissolves a specific compound and a polymer. Among them, it is preferable to use the following solvent (also referred to as A-type solvent).

[0125] For example, N,N-dimethylformamide, N,N-dimethylacetamide, N-methyl-2-pyrrolidone, N-ethyl-2-pyrrolidone, dimethyl sulfoxide, γ-butyrolactone, 1,3-dimethyl-2-imidazolidinone, methyl ethyl ketone, cyclohexanone, cyclopentanone, 4-hydroxy-4-methyl-2-pentanone, etc. Among them, N-methyl-2-pyrrolidone, N-ethyl-2-pyrrolidone or γ-butyrolactone is preferred. In addition, they can be used alone or in combination.

[0126] When the solubility of a specific polymer in a solvent is high, the following solvent (also referred to as a type B solvent) can be used.

[0127] Specific examples of the type B solvent include the type B solvents described on pages 58 to 60 of International Publication WO2014 / 171493 (published on October 23, 2014). Among them, 1-hexanol, cyclohexanol, 1,2-ethylene glycol, 1,2-propylene glycol, propylene glycol monobutyl ether, ethylene glycol monobutyl ether, dipropylene glycol dimethyl ether, cyclohexanone, cyclopentanone, or the above-mentioned formulas [D1] to [D3] are preferred.

[0128] Moreover, when using these B type solvents, it is preferable to use together with N-methyl-2-pyrrolidone, N-ethyl-2-pyrrolidone or γ-butyrolactone which is the above-mentioned A type solvent for the purpose of improving the coating property of a liquid crystal aligning agent.

[0129] These B-type solvents can improve the coating properties and surface smoothness of the liquid crystal alignment film when the liquid crystal alignment agent is applied. Therefore, when a polyimide precursor, polyimide, polyamide or polyester is used in a specific polymer, it is preferably used in combination with the A-type solvent. At this time, the B-type solvent is preferably 1 to 99% by mass of all solvents contained in the liquid crystal alignment agent. Among them, it is preferably 10 to 99% by mass. More preferably, it is 20 to 95% by mass.

[0130] In order to improve the film strength of the liquid crystal alignment film, it is preferred to introduce at least one compound (also collectively referred to as a specific crosslinking compound) selected from epoxy, isocyanate, oxetane, cyclocarbonate, hydroxyl, hydroxyalkyl and lower alkoxyalkyl groups into the liquid crystal alignment agent. In this case, the compound needs to have two or more of these groups.

[0131] Specific examples of the crosslinkable compound having an epoxy group or an isocyanate group include crosslinkable compounds having an epoxy group or an isocyanate group described on pages 63 to 64 of International Publication WO2014 / 171493 (published on October 23, 2014).

[0132] Specific examples of the crosslinkable compound having an oxetane group include crosslinkable compounds of formula [4a] to [4k] described on pages 58 to 59 of International Publication WO2011 / 132751 (published on October 27, 2011).

[0133] Specific examples of the crosslinkable compound having a cyclic carbonate group include crosslinkable compounds of formula [5-1] to [5-42] described on pages 76 to 82 of International Publication WO2012 / 014898 (published on February 2, 2012).

[0134] Specific examples of crosslinking compounds having a hydroxyl group, a hydroxyalkyl group, and a lower alkoxyalkyl group include melamine derivatives or benzoguanamine derivatives described on pages 65 to 66 of International Publication WO2014 / 171493 (published on October 23, 2014), and crosslinking compounds of formulas [6-1] to [6-48] described on pages 62 to 66 of International Publication WO2011 / 132751 (published on October 27, 2011).

[0135] The specific crosslinking compound in the liquid crystal aligning agent is preferably used in an amount of 0.1 to 100 parts by mass relative to 100 parts by mass of all polymer components, more preferably 0.1 to 50 parts by mass, and particularly preferably 1 to 30 parts by mass in order to allow the crosslinking reaction to proceed and achieve the desired effect.

[0136] As long as the effects of the present invention are not affected, the liquid crystal aligning agent may include compounds that improve the uniformity of the film thickness and surface smoothness of the liquid crystal aligning film when the liquid crystal aligning agent is applied, and compounds that enhance the adhesion between the liquid crystal aligning film and the substrate may also be used.

[0137] As compounds that improve the uniformity of the film thickness and the surface smoothness of the liquid crystal alignment film, fluorine-based surfactants, silicone-based surfactants, or nonionic surfactants can be cited. Specifically, surfactants described on page 67 of International Publication WO2014 / 171493 (published on October 23, 2014) can be cited. In addition, the usage ratio is preferably 0.01 to 2 parts by mass relative to 100 parts by mass of all polymer components. More preferably, it is 0.01 to 1 part by mass.

[0138] Specific examples of compounds that enhance the adhesion between the liquid crystal alignment film and the substrate include compounds described on pages 67 to 69 of International Publication WO2014 / 171493 (published on October 23, 2014). In addition, the usage ratio is preferably 0.1 to 30 parts by mass, more preferably 1 to 20 parts by mass, relative to 100 parts by mass of all polymer components.

[0139] In the liquid-crystal aligning agent, in addition to the compounds other than those described above, a dielectric or a conductive substance for the purpose of changing the electrical properties such as the dielectric constant and conductivity of the liquid crystal aligning film may be added.

[0140] <Liquid crystal alignment film / liquid crystal display element>

[0141] The liquid crystal aligning agent can be used as a liquid crystal aligning film by applying it on a substrate, baking it, and then performing an alignment treatment by rubbing, light irradiation, etc. Moreover, in the case of vertical alignment applications, it can be used as a liquid crystal aligning film even without performing an alignment treatment.

[0142] As the substrate used at this time, there is no particular limitation as long as it is a substrate with high transparency. In addition to glass substrates, plastic substrates such as acrylic substrates, polycarbonate substrates, and PET (polyethylene terephthalate) substrates can also be used, and further, their films can also be used. In addition, from the viewpoint of process simplification, it is preferred to use metal electrodes and organic conductive films such as ITO electrodes, IZO (Indium Zinc Oxide: Indium Zinc Oxide) electrodes and IGZO (Indium Gallium Zinc Oxide: Indium Gallium Zinc Oxide) electrodes formed for liquid crystal driving. In addition, in the case of a reflective liquid crystal display element, if only a single-sided substrate is used, a substrate formed with a metal or dielectric multilayer film such as a silicon wafer or aluminum can be used.

[0143] The coating method of the liquid crystal alignment agent is not particularly limited, but is generally performed industrially by screen printing, offset printing, flexographic printing or inkjet method, etc. As other coating methods, there are dipping method, roll coating method, slit coating method, spin coating method or spray method, etc., which can be used according to the purpose.

[0144] After the liquid crystal alignment agent is coated on the substrate, the solvent can be evaporated at a temperature of 30 to 300° C., preferably 30 to 250° C., to form a liquid crystal alignment film, depending on the solvent used for the liquid crystal alignment agent.

[0145] If the thickness of the liquid crystal alignment film after firing is too thick, it becomes disadvantageous in terms of power consumption of the liquid crystal display element, and if the thickness is too thin, the reliability of the liquid crystal display element may decrease. Therefore, it is preferably 5 to 300 nm, and more preferably 10 to 200 nm.

[0146] When the liquid crystal is horizontally aligned or tiltedly aligned, the liquid crystal alignment film after baking is processed by rubbing or irradiation with polarized ultraviolet rays.

[0147] The liquid crystal used for the liquid crystal display element is not particularly limited. For example, nematic liquid crystal, smectic liquid crystal or cholesteric liquid crystal can be used. In this case, liquid crystal with positive or negative dielectric anisotropy can be selected according to the method of the liquid crystal display element. In addition, a guest-host liquid crystal display element in which a dichroic dye is dissolved in the liquid crystal can also be used.

[0148] The method for injecting liquid crystal is not particularly limited, for example, the following methods can be cited. That is, a pair of substrates formed with a liquid crystal alignment film is prepared, and a portion of the four sheets of the substrate on one side is removed to apply a sealant, and then the substrate on the other side is bonded in such a way that the liquid crystal alignment film surface becomes the inner side, and an empty cell (cell) is made. Then, a method of injecting liquid crystal under reduced pressure from a position where a sealant is not applied to obtain a liquid crystal injection unit can be cited. In addition, the following method can also be cited: a pair of substrates formed with a liquid crystal alignment film are prepared, and liquid crystal is dripped on the top of the substrate on one side by ODF (One Drop Filling: liquid crystal dripping) method, inkjet method, etc., and then, the substrate on the other side is bonded to obtain a liquid crystal injection unit.

[0149] The method of controlling the gap of the liquid crystal display element is not particularly limited, and examples thereof include: a method of introducing a spacer of a target size into the liquid crystal, a method of applying on a substrate having a column spacer of a target size, a method of using a liquid crystal containing a column spacer of a target size, etc.

[0150] The size of the gap of the liquid crystal display element is preferably 1 to 100 μm. More preferably, it is 1 to 50 μm. Especially preferably, it is 2 to 30 μm. If the gap is too small, the contrast of the liquid crystal display element will decrease, and if the gap is too large, the driving voltage of the element will increase.

[0151] Example

[0152] Hereinafter, the present invention will be described in further detail with reference to Examples, but the present invention is not limited thereto.

[0153] The abbreviations used below are as follows.

[0154] "Specific compounds"

[0155] T1: Phosmer PE (manufactured by DAP).

[0156] T2: KAYAMER PM-21 (manufactured by Nippon Kayaku Co., Ltd.).

[0157] "Compounds for polyimide polymers"

[0158] <Specific diamine>

[0159]

[0160] <Other diamines>

[0161]

[0162] <Tetracarboxylic acid component>

[0163]

[0164] "Compounds for polysiloxane polymers"

[0165] E1: 3-methacryloxypropyltrimethoxysilane. E2: tetraethoxysilane.

[0166]

[0167] "Cross-linking compounds"

[0168]

[0169] "Solvent"

[0170] NMP: N-methyl-2-pyrrolidone.

[0171] NEP: N-ethyl-2-pyrrolidone.

[0172] BCS: ethylene glycol monobutyl ether.

[0173] PB: Propylene glycol monobutyl ether.

[0174] ECS: Ethylene glycol monoethyl ether.

[0175] EC: diethylene glycol monoethyl ether.

[0176] "Determination of Molecular Weight of Polyimide-Based Polymers"

[0177] The measurement was performed as follows using a room temperature gel permeation chromatography (GPC) apparatus (GPC-101) (manufactured by Showa Denko K.K.) and columns (KD-803 and KD-805) (manufactured by Shodex K.K.).

[0178] Column temperature: 50°C.

[0179] Eluent: N, N-dimethylformamide (as an additive, lithium bromide monohydrate (LiBr·H 2 O) is 30 mmol / L (liter), phosphoric acid / anhydrous crystals (orthophosphoric acid) is 30 mmol / L, and tetrahydrofuran (THF) is 10 ml / L).

[0180] Flow rate: 1.0 ml / min.

[0181] Standard samples for preparing the calibration curve: TSK standard polyethylene oxide (molecular weight: about 900,000, 150,000, 100,000 and 30,000) (manufactured by Tosoh Corporation) and polyethylene glycol (molecular weight: about 12,000, 4,000 and 1,000) (manufactured by Polymer Laboratories).

[0182] "Determination of the imidization ratio of polyimide-based polymers"

[0183] To NMR (nuclear magnetic resonance) sample tube (NMR standard sample tube, 20 mg of polyimide powder was added to 1% ethanol (made by Kusano Scientific Co., Ltd.), deuterated dimethyl sulfoxide (DMSO-d6, 0.05 mass% TMS (tetramethylsilane) mixture) (0.53 ml) was added, and ultrasonic waves were applied to completely dissolve it. The solution was measured for 500 MHz proton NMR using an NMR measuring machine (JNW-ECA500) (made by JEOL DATUM Co., Ltd.). The imidization rate was calculated as follows: the proton derived from the structure that does not change before and after imidization is determined as the reference proton, and the peak integral value of the proton and the proton peak integral value derived from the NH group of the amide acid appearing near 9.5 ppm to 10.0 ppm are used to calculate it using the following formula.

[0184] Imidization rate (%) = (1-α·x / y) × 100

[0185] x is the peak integral value of protons derived from NH groups of amic acid, y is the peak integral value of reference protons, and α is the number ratio of reference protons to protons of one NH group of amic acid in the case of polyamic acid (imidation ratio 0%).

[0186] "Synthesis of polyimide polymers"

[0187] <Synthesis example 1>

[0188] C2 (1.12 g, 4.48 mol), A1 (2.43 g, 9.19 mmol), B1 (0.50 g, 4.62 mmol) and B2 (2.63 g, 9.18 mmol) were mixed in NMP (20.4 g), reacted at 80° C. for 4 hours, then C1 (3.50 g, 17.8 mmol) and NMP (10.2 g) were added, reacted at 40° C. for 6 hours, and a polyamic acid solution (1) having a resin solid content concentration of 25% by mass was obtained. The number average molecular weight (also referred to as Mn) of the polyamic acid was 24200, and the weight average molecular weight (also referred to as Mw) was 78500.

[0189] <Synthesis example 2>

[0190] NMP was added to the polyamic acid solution (1) (20.0 g) obtained by the method of Synthesis Example 1 and diluted to 6 mass %, and then acetic anhydride (2.40 g) and pyridine (1.55 g) were added as imidization catalysts, and the mixture was reacted at 60° C. for 2 hours. The reaction solution was put into methanol (450 ml), and the obtained precipitate was filtered out. The precipitate was washed with methanol and dried under reduced pressure at 100° C. to obtain a polyimide powder (2). The imidization rate of the polyimide was 62%, Mn was 21500, and Mw was 49200.

[0191] <Synthesis Example 3>

[0192] C2 (1.87 g, 7.47 mol), A1 (3.05 g, 11.5 mmol) and B3 (2.93 g, 7.70 mmol) were mixed in NMP (20.1 g), and reacted at 80° C. for 4 hours, and then C1 (2.20 g, 11.2 mmol) and NMP (10.1 g) were added, and reacted at 40° C. for 6 hours to obtain a polyamic acid solution (3) having a resin solid content concentration of 25% by mass. The polyamic acid had an Mn of 20100 and an Mw of 68200.

[0193] <Synthesis example 4>

[0194] NMP was added to the polyamic acid solution (3) (20.0 g) obtained by the method of Synthesis Example 3 and diluted to 6 mass %, and then acetic anhydride (2.35 g) and pyridine (1.50 g) were added as imidization catalysts, and the mixture was reacted at 60° C. for 1.5 hours. The reaction solution was put into methanol (450 ml) and the obtained precipitate was filtered out. The precipitate was washed with methanol and dried under reduced pressure at 100° C. to obtain a polyimide powder (4). The imidization rate of the polyimide was 55%, Mn was 17900, and Mw was 43200.

[0195] <Synthesis example 5>

[0196] C2 (1.11 g, 4.44 mol), A2 (0.93 g, 4.57 mmol), B1 (0.25 g, 2.31 mmol) and B3 (1.73 g, 4.55 mmol) were mixed in NEP (10.6 g), reacted at 80° C. for 4 hours, then C1 (1.30 g, 6.63 mmol) and NEP (5.31 g) were added, and reacted at 40° C. for 6 hours to obtain a polyamic acid solution (5) having a resin solid content concentration of 25% by mass. The polyamic acid had an Mn of 22,900 and an Mw of 71,200.

[0197] <Synthesis Example 6>

[0198] C3 (2.30 g, 10.3 mmol), A1 (0.56 g, 2.12 mmol), A2 (0.43 g, 2.12 mmol) and B2 (1.82 g, 6.36 mmol) were mixed in NMP (15.3 g) and reacted at 40° C. for 12 hours to obtain a polyamic acid solution (6) having a resin solid content concentration of 25% by mass. The polyamic acid had an Mn of 20,200 and an Mw of 54,400.

[0199] <Synthesis Example 7>

[0200] C3 (2.30 g, 10.3 mmol), A2 (1.72 g, 8.46 mmol) and B4 (1.04 g, 2.11 mmol) were mixed in NMP (15.2 g) and reacted at 40° C. for 12 hours to obtain a polyamic acid solution (7) having a resin solid content concentration of 25% by mass. The polyamic acid had an Mn of 17100 and an Mw of 46800.

[0201] <Synthesis example 8>

[0202] Under a nitrogen atmosphere, A1 (0.51 g, 1.93 mmol), B1 (0.31 g, 2.87 mmol), B2 (1.39 g, 4.85 mmol), pyridine (1.88 g) and NMP (15.1 g) were added, stirred to dissolve, C4 (2.80 g, 9.43 mmol) was added, and the mixture was reacted at 15 ° C for 15 hours. After that, acryloyl chloride (0.04 g) was added, and the mixture was reacted at 15 ° C for 4 hours. The reaction solution was put into water (500 g), and the obtained precipitate was filtered out. The precipitate was washed with isopropanol and dried under reduced pressure at 100 ° C to obtain a polyamic acid alkyl ester powder (8). The Mn of the polyamic acid alkyl ester is 18500 and the Mw is 40100.

[0203] <Synthesis Example 9>

[0204] C2 (1.31 g, 5.24 mol), B1 (1.75 g, 16.2 mmol) and B2 (3.08 g, 10.8 mmol) were mixed in NMP (20.5 g), reacted at 80° C. for 4 hours, then C1 (4.10 g, 20.9 mmol) and NMP (10.2 g) were added, and reacted at 40° C. for 6 hours to obtain a polyamic acid solution (9) having a resin solid content concentration of 25% by mass. The polyamic acid had an Mn of 27,500 and an Mw of 84,100.

[0205] <Synthesis Example 10>

[0206] NMP was added to the polyamic acid solution (9) (20.0 g) obtained by the method of Synthesis Example 9 and diluted to 6 mass %, and then acetic anhydride (2.40 g) and pyridine (1.55 g) were added as imidization catalysts, and the mixture was reacted at 60° C. for 2 hours. The reaction solution was put into methanol (450 ml), and the obtained precipitate was filtered out. The precipitate was washed with methanol and dried under reduced pressure at 100° C. to obtain a polyimide powder (10). The imidization rate of the polyimide was 61%, Mn was 23000, and Mw was 53100.

[0207] <Synthesis Example 11>

[0208] C2 (2.30 g, 9.19 mol), B1 (1.53 g, 14.1 mmol) and B3 (3.60 g, 9.46 mmol) were mixed in NMP (20.3 g), reacted at 80° C. for 4 hours, then C1 (2.70 g, 13.8 mmol) and NMP (10.1 g) were added, and reacted at 40° C. for 6 hours to obtain a polyamic acid solution (11) having a resin solid content concentration of 25% by mass. The polyamic acid had an Mn of 21,900 and an Mw of 70,900.

[0209] <Synthesis Example 12>

[0210] NMP was added to the polyamic acid solution (11) (20.0 g) obtained by the method of Synthesis Example 11 and diluted to 6 mass %, and then acetic anhydride (2.35 g) and pyridine (1.50 g) were added as imidization catalysts, and the mixture was reacted at 60° C. for 1.5 hours. The reaction solution was put into methanol (450 ml) and the obtained precipitate was filtered out. The precipitate was washed with methanol and dried under reduced pressure at 100° C. to obtain a polyimide powder (12). The imidization rate of the polyimide was 56%, Mn was 18900, and Mw was 46100.

[0211] Table 1 shows the polyimide polymers obtained in the synthesis examples.

[0212] [Table 1]

[0213]

[0214] *1: Polyamic acid.

[0215] *2: Polyamic acid alkyl ester.

[0216] "Synthesis of polysiloxane polymers"

[0217] <Synthesis Example 13>

[0218] ECS (28.3 g), E1 (7.45 g), E2 (33.6 g) and E3 (4.10 g) were mixed in a 200 ml four-necked reaction flask equipped with a thermometer and a reflux tube to prepare a solution of alkoxysilane monomers. A solution prepared by mixing ECS ​​(14.2 g), water (10.8 g) and oxalic acid (0.70 g) as a catalyst was added dropwise to the solution at 25°C for 30 minutes, and then stirred at 25°C for 30 minutes. After that, the mixture was heated in an oil bath and refluxed for 30 minutes, and then cooled to obtain SiO 2 The converted concentration is 12% by mass of the polysiloxane solution (1).

[0219] <Synthesis Example 14>

[0220] EC (25.4 g), E1 (19.9 g), E2 (21.1 g) and E3 (8.20 g) were mixed in a 200 ml four-necked reaction flask equipped with a thermometer and a reflux tube to prepare a solution of alkoxysilane monomers. A solution prepared by mixing EC (12.7 g), water (10.8 g) and oxalic acid (1.10 g) as a catalyst was added dropwise to the solution at 25°C for 30 minutes, and then stirred at 25°C for 30 minutes. After that, the mixture was heated in an oil bath and refluxed for 30 minutes, and then cooled to obtain SiO2 The converted concentration is 12% by mass of the polysiloxane solution (2).

[0221] Table 2 shows the polysiloxane polymers obtained in the synthesis examples.

[0222] [Table 2]

[0223]

[0224] "Manufacturing of liquid crystal alignment agent"

[0225] Production examples of the liquid-crystal aligning agent are described in the following Examples 1 to 11 and Comparative Examples 1 to 12. In addition, this liquid-crystal aligning agent was also used for evaluation.

[0226] Tables 3 and 4 show the obtained liquid-crystal aligning agents.

[0227] "Storage stability test of liquid crystal alignment agent"

[0228] The storage stability test was performed using the liquid crystal aligning agent obtained in the examples and comparative examples. Specifically, the liquid crystal aligning agent was filtered under pressure using a membrane filter with a pore size of 1 μm and stored at -15°C for 72 hours. Then, the turbidity and precipitate in the liquid crystal aligning agent were confirmed by visual observation. As a result, no turbidity or precipitate was observed in all the liquid crystal aligning agents of the examples and comparative examples, and all were uniform solutions.

[0229] "Evaluation of fit"

[0230] The liquid crystal alignment agent obtained in the embodiment and the comparative example was applied to the ITO surface of a 100×100 mm PET substrate with an ITO electrode (vertical: 100 mm, horizontal: 100 mm, thickness: 0.1 mm) washed with pure water by spin coating, and heated on a hot plate at 120° C. for 2 minutes to obtain an ITO substrate with a liquid crystal alignment film having a film thickness of 100 nm. Two pieces of the ITO substrate with a liquid crystal alignment film were prepared and cut out into a size of 100×20 mm (vertical×horizontal).

[0231] Next, a 6 μm spacer was applied to the liquid crystal alignment film surface of one substrate, and a sealant (723K1) (manufactured by Kyoritsu Chemical Industry Co., Ltd.) was applied to the liquid crystal alignment film surface of the other substrate, and the two substrates were bonded together in such a way that the liquid crystal alignment film surfaces of the two substrates faced each other. At this time, the amount of sealant applied was adjusted so that the area of ​​the sealant after bonding became 5×50 mm (vertical×horizontal). Then, an illumination of 20 mW / cm 2 The metal halide lamp irradiates the bonded substrates at a wavelength of 365 nm, which is 3 J / cm2 The film was irradiated with ultraviolet rays, and then heat-treated at 120° C. for 60 minutes in a heat circulation type clean oven to produce a cell for adhesion evaluation.

[0232] The evaluation of the adhesion was performed using a desktop precision universal testing machine (AGS-X 500N) (manufactured by Shimadzu Corporation). Specifically, after the upper and lower ends of the obtained unit were fixed, the breaking strength (N) when stretched in the vertical direction was measured. In terms of evaluation, the larger the value of the breaking strength, the better the adhesion, that is, it was set as excellent in this evaluation.

[0233] The results are shown in Tables 5 and 6.

[0234] "Production of liquid crystal display elements and evaluation of their resistance to constant temperature and humidity"

[0235] The liquid crystal alignment agent obtained in the embodiment and the comparative example was pressure filtered using a membrane filter with a pore size of 1 μm, and spin-coated on the ITO surface of a substrate with an ITO electrode (40 mm in length × 30 mm in width, 0.7 mm in thickness) that had been cleaned with pure water and IPA. The solution was heated on a heating plate at 120°C for 2 minutes, and then heated at 230°C for 30 minutes in a thermal circulation clean oven to obtain an ITO substrate with a liquid crystal alignment film with a thickness of 100 nm.

[0236] Next, for the substrates obtained in Example 1, Example 2, Example 7, Example 9, Comparative Example 1, Comparative Example 2, Comparative Example 5, Comparative Example 6, Comparative Example 9 and Comparative Example 10, the liquid crystal alignment film surfaces of the substrates were subjected to brushing treatment in a brushing device with a roller diameter of 120 mm, using a rayon cloth, under the conditions of a roller rotation speed of 500 rpm, a roller travel speed of 30 mm / sec, and a pressing amount of 0.3 mm. No other brushing treatment was performed.

[0237] Then, prepare two substrates that have been brushed or not, apply a 4μm spacer to the liquid crystal alignment film surface of one substrate, and apply a sealant (XN-1500T) (manufactured by Kyoritsu Chemical Industry Co., Ltd.) to the liquid crystal alignment film surfaces of the four sides of the other substrate, and bond the two substrates in such a way that the liquid crystal alignment film surfaces of the two substrates face each other. At this time, bond the substrates in such a way that the rubbing directions of the substrates are opposite. Next, heat treatment is performed at 120°C for 90 minutes in a heat cycle clean oven to produce an empty cell. Liquid crystal is injected into the empty cell by a reduced pressure injection method, and the injection port is sealed to obtain a liquid crystal cell. It should be noted that in Example 1, Example 2, Example 7, Example 9, Comparative Example 1, Comparative Example 2, Comparative Example 5, Comparative Example 6, Comparative Example 9 and Comparative Example 10, the liquid crystal used is a positive liquid crystal (MLC-2003) (manufactured by MERCK); in Examples 3 to 6, Example 8, Example 10, Example 11, Comparative Example 3, Comparative Example 4, Comparative Example 7, Comparative Example 8, Comparative Example 11 and Comparative Example 12, the liquid crystal used is a negative liquid crystal (MLC-6608) (manufactured by MERCK).

[0238] By observation using a polarizing microscope (ECLIPSE E600WPOL) (manufactured by Nikon Corporation), it was confirmed that the liquid crystal cells obtained in the examples and comparative examples all showed uniform liquid crystal orientation.

[0239] Then, the liquid crystal cell was kept in a constant temperature and humidity chamber at a temperature of 80°C and a humidity of 90%RH for 48 hours, and the peeling of the liquid crystal cell and the presence or absence of bubbles were confirmed. Specifically, the liquid crystal cell that did not produce peeling (the state of peeling between the liquid crystal alignment film and the sealant and between the liquid crystal alignment film and the ITO electrode) and the liquid crystal cell that did not produce bubbles in the liquid crystal cell were set as excellent in this evaluation (good display in the table). At this time, in Example 5 and Example 6, in addition to the standard test described, as an emphasis test, it was confirmed after being kept in a constant temperature and humidity chamber at a temperature of 80°C and a humidity of 90%RH for 96 hours. It should be noted that the evaluation method is the same as above.

[0240] The results are shown in Tables 5 and 6.

[0241] <Example 1>

[0242] T1 (0.13 g), NMP (23.8 g) and BCS (7.83 g) were added to the polyamic acid solution (1) (10.0 g) having a resin solid content concentration of 25% by mass obtained in Synthesis Example 1, and the mixture was stirred at 25° C. for 15 hours to obtain a liquid crystal aligning agent (1). Abnormalities such as turbidity and precipitation were not observed in the liquid crystal aligning agent, and it was confirmed to be a uniform solution.

[0243] <Example 2>

[0244] NMP (31.3 g) was added to the polyimide powder (2) (2.50 g) obtained in Synthesis Example 2, and the mixture was stirred at 60° C. for 24 hours to dissolve the mixture. T1 (0.13 g) and BCS (7.83 g) were added to the solution, and the mixture was stirred at 25° C. for 15 hours to obtain a liquid crystal aligning agent (2). No abnormalities such as turbidity and precipitation were observed in the liquid crystal aligning agent, and the solution was confirmed to be a uniform solution.

[0245] <Example 3>

[0246] T2 (0.18 g), NMP (16.0 g) and BCS (15.6 g) were added to the polyamic acid solution (3) (10.0 g) having a resin solid content concentration of 25% by mass obtained in Synthesis Example 3, and the mixture was stirred at 25° C. for 15 hours to obtain a liquid crystal aligning agent (3). Abnormalities such as turbidity and precipitation were not observed in the liquid crystal aligning agent, and it was confirmed to be a uniform solution.

[0247] <Example 4>

[0248] NMP (23.5 g) was added to the polyimide powder (4) (2.50 g) obtained in Synthesis Example 4, and the mixture was stirred at 60° C. for 24 hours to dissolve the mixture. T2 (0.18 g), BCS (3.92 g) and PB (11.8 g) were added to the solution, and the mixture was stirred at 25° C. for 15 hours to obtain a liquid crystal aligning agent (4). No abnormalities such as turbidity and precipitation were observed in the liquid crystal aligning agent, and the liquid crystal aligning agent was confirmed to be a uniform solution.

[0249] <Example 5>

[0250] T2 (0.13 g), NEP (16.0 g) and PB (15.7 g) were added to the polyamic acid solution (5) (10.0 g) having a resin solid content concentration of 25% by mass obtained in Synthesis Example 5, and the mixture was stirred at 25° C. for 15 hours to obtain a liquid crystal aligning agent (5). Abnormalities such as turbidity and precipitation were not observed in the liquid crystal aligning agent, and it was confirmed to be a uniform solution.

[0251] <Example 6>

[0252] T2 (0.13 g), K1 (0.13 g), NEP (16.0 g) and PB (15.7 g) were added to the polyamic acid solution (5) (10.0 g) having a resin solid content concentration of 25% by mass obtained in Synthesis Example 5, and the mixture was stirred at 25° C. for 15 hours to obtain a liquid crystal aligning agent (6). No abnormalities such as turbidity and precipitation were observed in the liquid crystal aligning agent, and it was confirmed to be a uniform solution.

[0253] <Example 7>

[0254] T1 (0.08 g), K2 (0.08 g), NMP (23.8 g) and PB (7.83 g) were added to the polyamic acid solution (6) (10.0 g) having a resin solid content concentration of 25% by mass obtained in Synthesis Example 6, and the mixture was stirred at 25° C. for 15 hours to obtain a liquid crystal aligning agent (7). No abnormalities such as turbidity and precipitation were observed in the liquid crystal aligning agent, and it was confirmed to be a uniform solution.

[0255] <Example 8>

[0256] T1 (0.08 g), T2 (0.08 g), K2 (0.18 g), NMP (19.9 g) and BCS (11.8 g) were added to the polyamic acid solution (7) (10.0 g) having a resin solid content concentration of 25% by mass obtained in Synthesis Example 7, and the mixture was stirred at 25° C. for 15 hours to obtain a liquid crystal aligning agent (8). Abnormalities such as turbidity and precipitation were not observed in the liquid crystal aligning agent, and it was confirmed to be a uniform solution.

[0257] <Example 9>

[0258] NMP (31.3 g) was added to the polyamic acid alkyl ester powder (8) (2.50 g) obtained in Synthesis Example 8, and the mixture was stirred at 40° C. for 24 hours to dissolve the mixture. T2 (0.13 g), K1 (0.08 g) and BCS (7.83 g) were added to the solution, and the mixture was stirred at 25° C. for 15 hours to obtain a liquid crystal aligning agent (9). No abnormalities such as turbidity and precipitation were observed in the liquid crystal aligning agent, and the liquid crystal aligning agent was confirmed to be a uniform solution.

[0259] <Example 10>

[0260] T1 (0.04 g), ECS (2.48 g) and BCS (7.52 g) were added to the polysiloxane solution (1) (10.0 g) obtained in Synthesis Example 13, and the mixture was stirred at 25° C. for 15 hours to obtain a liquid crystal aligning agent (10). Abnormalities such as turbidity and precipitation were not observed in the liquid crystal aligning agent, and it was confirmed to be a uniform solution.

[0261] <Example 11>

[0262] T2 (0.06 g), ECS (2.48 g) and PB (7.52 g) were added to the polysiloxane solution (2) (10.0 g) obtained in Synthesis Example 14, and the mixture was stirred at 25° C. for 15 hours to obtain a liquid crystal aligning agent (11). Abnormalities such as turbidity and precipitation were not observed in the liquid crystal aligning agent, and it was confirmed to be a uniform solution.

[0263] <Comparative Example 1>

[0264] NMP (23.8 g) and BCS (7.83 g) were added to the polyamic acid solution (9) (10.0 g) having a resin solid content concentration of 25% by mass obtained in Synthesis Example 9, and the mixture was stirred at 25° C. for 15 hours to obtain a liquid crystal aligning agent (12). Abnormalities such as turbidity and precipitation were not observed in the liquid crystal aligning agent, and it was confirmed to be a uniform solution.

[0265] <Comparative Example 2>

[0266] NMP (31.3 g) was added to the polyimide powder (10) (2.50 g) obtained in Synthesis Example 10, and the mixture was stirred at 60° C. for 24 hours to dissolve. BCS (7.83 g) was added to the solution, and the mixture was stirred at 25° C. for 15 hours to obtain a liquid crystal aligning agent (13). No abnormalities such as turbidity and precipitation were observed in the liquid crystal aligning agent, and the solution was confirmed to be a uniform solution.

[0267] <Comparative Example 3>

[0268] NMP (16.0 g) and BCS (15.6 g) were added to the polyamic acid solution (11) (10.0 g) having a resin solid content concentration of 25% by mass obtained in Synthesis Example 11, and stirred at 25° C. for 15 hours to obtain a liquid crystal aligning agent (14). Abnormalities such as turbidity and precipitation were not observed in the liquid crystal aligning agent, and it was confirmed to be a uniform solution.

[0269] <Comparative Example 4>

[0270] NMP (23.5 g) was added to the polyimide powder (12) (2.50 g) obtained in Synthesis Example 12, and the mixture was stirred at 60° C. for 24 hours to dissolve. BCS (3.92 g) and PB (11.8 g) were added to the solution, and the mixture was stirred at 25° C. for 15 hours to obtain a liquid crystal aligning agent (15). No abnormalities such as turbidity and precipitation were observed in the liquid crystal aligning agent, and the solution was confirmed to be a uniform solution.

[0271] <Comparative Example 5>

[0272] T1 (0.13 g), NMP (23.8 g) and BCS (7.83 g) were added to the polyamic acid solution (9) (10.0 g) having a resin solid content concentration of 25% by mass obtained in Synthesis Example 9, and the mixture was stirred at 25° C. for 15 hours to obtain a liquid crystal aligning agent (16). Abnormalities such as turbidity and precipitation were not observed in the liquid crystal aligning agent, and it was confirmed to be a uniform solution.

[0273] <Comparative Example 6>

[0274] NMP (31.3 g) was added to the polyimide powder (10) (2.50 g) obtained in Synthesis Example 10, and the mixture was stirred at 60° C. for 24 hours to dissolve the mixture. T1 (0.13 g) and BCS (7.83 g) were added to the solution, and the mixture was stirred at 25° C. for 15 hours to obtain a liquid crystal aligning agent (17). No abnormalities such as turbidity and precipitation were observed in the liquid crystal aligning agent, and the solution was confirmed to be a uniform solution.

[0275] <Comparative Example 7>

[0276] T2 (0.18 g), NMP (16.0 g) and BCS (15.6 g) were added to the polyamic acid solution (11) (10.0 g) having a resin solid content concentration of 25% by mass obtained in Synthesis Example 11, and the mixture was stirred at 25° C. for 15 hours to obtain a liquid crystal aligning agent (18). Abnormalities such as turbidity and precipitation were not observed in the liquid crystal aligning agent, and it was confirmed to be a uniform solution.

[0277] <Comparative Example 8>

[0278] NMP (23.5 g) was added to the polyimide powder (12) (2.50 g) obtained in Synthesis Example 12, and the mixture was stirred at 60° C. for 24 hours to dissolve the mixture. T2 (0.18 g), BCS (3.92 g) and PB (11.8 g) were added to the solution, and the mixture was stirred at 25° C. for 15 hours to obtain a liquid crystal aligning agent (19). No abnormalities such as turbidity and precipitation were observed in the liquid crystal aligning agent, and the solution was confirmed to be a uniform solution.

[0279] <Comparative Example 9>

[0280] NMP (23.8 g) and BCS (7.83 g) were added to the polyamic acid solution (1) (10.0 g) having a resin solid content concentration of 25% by mass obtained in Synthesis Example 1, and stirred at 25° C. for 15 hours to obtain a liquid crystal aligning agent (20). Abnormalities such as turbidity and precipitation were not observed in the liquid crystal aligning agent, and it was confirmed to be a uniform solution.

[0281] <Comparative Example 10>

[0282] NMP (31.3 g) was added to the polyimide powder (2) (2.50 g) obtained in Synthesis Example 2, and the mixture was stirred at 60° C. for 24 hours to dissolve. BCS (7.83 g) was added to the solution, and the mixture was stirred at 25° C. for 15 hours to obtain a liquid crystal aligning agent (21). No abnormalities such as turbidity and precipitation were observed in the liquid crystal aligning agent, and the solution was confirmed to be a uniform solution.

[0283] <Comparative Example 11>

[0284] NMP (16.0 g) and BCS (15.6 g) were added to the polyamic acid solution (3) (10.0 g) having a resin solid content concentration of 25% by mass obtained in Synthesis Example 3, and the mixture was stirred at 25° C. for 15 hours to obtain a liquid crystal aligning agent (22). Abnormalities such as turbidity and precipitation were not observed in the liquid crystal aligning agent, and it was confirmed to be a uniform solution.

[0285] <Comparative Example 12>

[0286] NMP (23.5 g) was added to the polyimide powder (4) (2.50 g) obtained in Synthesis Example 4, and the mixture was stirred at 60° C. for 24 hours to dissolve. BCS (3.92 g) and PB (11.8 g) were added to the solution, and the mixture was stirred at 25° C. for 15 hours to obtain a liquid crystal aligning agent (23). No abnormalities such as turbidity and precipitation were observed in the liquid crystal aligning agent, and the solution was confirmed to be a uniform solution.

[0287] <Example 1 to Example 11 and Comparative Example 1 to Comparative Example 12>

[0288] Using the liquid-crystal aligning agents (1) to (23), “evaluation of adhesion” and “production of a liquid crystal display element and evaluation of constant temperature and humidity resistance” were performed under the conditions described above.

[0289] [Table 3]

[0290] Example Liquid crystal alignment agent polymer Specific compound*3 Cross-linking compound*4 1 (1) Polyamic acid solution (1) T1(5) - 2 (2) Polyimide powder(2) T1(5) - 3 (3) Polyamic acid liquid (3) T2(7) - 4 (4) Polyimide powder(4) T2(7) - 5 (5) Polyamic acid solution (5) T2(5) - 6 (6) Polyamic acid solution (5) T2(5) K1(5) 7 (7) Polyamic acid solution (6) T1(3) K2(3) 8 (8) Polyamic acid solution (7) T1(3), T2(3) K2(7) 9 (9) Polyamic acid alkyl ester powder (8) T2(5) K1(3) 10 (10) Polysiloxane solution (1) T1(3) - 11 (11) Polysiloxane solution (2) T2(5) -

[0291] [Table 4]

[0292] Comparative Example Liquid crystal alignment agent polymer Specific compound*3 Cross-linking compound*4 1 (12) Polyamic acid solution (9) - - 2 (13) Polyimide powder(10) - - 3 (14) Polyamic acid solution (11) - - 4 (15) Polyimide Powder(12) - - 5 (16) Polyamic acid solution (9) T1(5) - 6 (17) Polyimide powder(10) T1(5) - 7 (18) Polyamic acid solution (11) T2(7) - 8 (19) Polyimide Powder(12) T2(7) - 9 (20) Polyamic acid solution (1) - - 10 (21) Polyimide powder(2) - - 11 (22) Polyamic acid solution (3) - - 12 (23) Polyimide powder(4) - -

[0293] *3: The numerical values ​​in parentheses represent the amount (parts by mass) of the specific compound introduced relative to 100 parts by mass of the polymer.

[0294] *4: The numerical values ​​in parentheses represent the amount (parts by mass) of the crosslinking compound introduced relative to 100 parts by mass of the polymer.

[0295] [Table 5]

[0296]

[0297] [Table 6]

[0298]

[0299] *5: Very small amount of bubbles were observed inside the device.

[0300] *6: Bubbles were observed inside the device (more than *5).

[0301] *7: A large number of bubbles were observed inside the device (more than *6).

[0302] According to the above results, the examples using the liquid crystal aligning agent containing the specific compound and the specific polymer have excellent adhesion compared with the comparative examples using the liquid crystal aligning agent containing neither or only one of them, and the liquid crystal unit does not peel off even when the liquid crystal unit is stored for a long time under high temperature and high humidity. Specifically, the comparisons under the same conditions are: Example 1 with Comparative Examples 1, 5 and 9; Example 2 with Comparative Examples 2, 6 and 10; Example 3 with Comparative Examples 3, 7 and 11; and Example 4 with Comparative Examples 4, 8 and 12.

[0303] Moreover, when the crosslinking compound was introduced into the liquid crystal aligning agent, in the stress test, bubbles were not generated in the liquid crystal cell.

[0304] And in the storage stability test of the liquid-crystal aligning agent, turbidity and precipitate were not observed in all Examples, and all of them were uniform solutions.

[0305] Industrial Applicability

[0306] By using a liquid crystal alignment film obtained by a liquid crystal alignment agent containing a compound having a specific structure and a polymer having a specific structure, it is possible to obtain a liquid crystal display element having high adhesion between substrates, and even if exposed to a harsh environment of high temperature and high humidity for a long time, it is possible to suppress the generation of bubbles in the liquid crystal display element and the peeling of the element. Therefore, it is applicable to liquid crystal display elements of smart phones, mobile phones, etc.

[0307] It should be noted that the entire contents of the specification, claims, and abstract of Japanese Patent Application No. 2019-042709 filed on Mar. 8, 2019 are incorporated herein by reference and incorporated as a disclosure of the specification of the present invention.

Claims

1. A liquid crystal alignment agent, wherein Containing the following components (A) and (B), Component (A): a compound of the following formula [1], Component (B): a polymer having at least one structure selected from the following formulas [2-a] to [2-e] and formula [2-i], T 1 represents the following formula [1-a] or formula [1-b], T 2 represents an alkylene group having 2 to 24 carbon atoms, wherein the alkylene group does not have any carbon atoms. 1 Any -CH2- adjacent to O is optionally replaced by -O-, -CO-, -COO-, -OCO-, -CONH-, -NHCO-, -NH- or -CON(CH3)-, Tm represents an integer of 1 to 2, Tn represents an integer of 1 to 2, wherein Tm+Tn is 3, 2. The liquid crystal alignment agent according to claim 1, wherein The compound of the formula [1] is any one of the following formulas [1a-1] to [1a-3], T a represents the above formula [1-a] or formula [1-b], T b Each of them represents an alkylene group having 2 to 18 carbon atoms, T c Indicates -COO- or -OCO-, T d represents an alkylene group having 2 to 12 carbon atoms, p1 represents an integer of 1 to 2, p2 represents an integer of 1 to 2, wherein p1+p2 is 3, and p3 represents an integer of 2 to 8.

3. The liquid crystal aligning agent according to claim 1 or 2, wherein The polymer is at least one selected from acrylic polymer, methacrylic polymer, novolac resin, polyhydroxystyrene, polyimide precursor, polyimide, polyamide, polyester, cellulose and polysiloxane.

4. The liquid crystal alignment agent according to claim 3, wherein The polymer contains a polyimide precursor or a polyimide obtained by using a diamine having at least one structure selected from the formulas [2-a] to [2-e] and the formula [2-i] as a part of a raw material.

5. The liquid crystal alignment agent according to claim 4, wherein The diamine has the structure of the following formula [2], X 1 represents a single bond, -O-, -NH-, -N(CH3)-, -CH2O-, -CONH-, -NHCO-, -CON(CH3)-, -N(CH3)CO-, -COO- or -OCO-, X 2 represents a single bond, an alkylene group having 1 to 18 carbon atoms, or an organic group having 6 to 24 carbon atoms having a cyclic group selected from a benzene ring, a cyclohexane ring, and a heterocyclic ring, wherein any hydrogen atom on the cyclic group is optionally substituted with an alkyl group having 1 to 3 carbon atoms, an alkoxy group having 1 to 3 carbon atoms, a fluorinated alkyl group having 1 to 3 carbon atoms, a fluorinated alkoxy group having 1 to 3 carbon atoms, or a fluorine atom, and X 3 represents a single bond, -O-, -NH-, -N(CH3)-, -CH2O-, -CONH-, -NHCO-, -CON(CH3)-, -N(CH3)CO-, -COO- or -OCO-, X 4 represents any one of the above formulas [2-a] to [2-e] and formula [2-i], and Xm represents an integer of 1 to 4.

6. The liquid crystal alignment agent according to claim 5, wherein The diamine is of the following formula [2a], X represents the above formula [2], and Xn represents an integer of 1 to 4.

7. The liquid crystal aligning agent according to any one of claims 4 to 6, wherein The diamine is at least one selected from the following formulas [2a-1] to [2a-12], n1 represents an integer of 1 to 12, n2 represents an integer of 0 to 12, and n3 represents an integer of 2 to 12.

8. The liquid crystal aligning agent according to any one of claims 4 to 6, wherein The polymer is a polyimide precursor or a polyimide, and the polyimide precursor or the polyimide is obtained by using a tetracarboxylic acid component of the following formula [3] as a part of a raw material, Z represents any one of the following formulas [3a] to [31], Z A ~Z D represent a hydrogen atom, a methyl group, a chlorine atom or a benzene ring, Z E and Z F represent a hydrogen atom or a methyl group, respectively.

9. The liquid crystal alignment agent according to claim 3, wherein The polymer comprises: a polysiloxane obtained by polycondensing an alkoxysilane of the following formula [A1]; or a polysiloxane obtained by polycondensing an alkoxysilane of the formula [A1] and an alkoxysilane of the following formula [A2], (A 1 ) m Si(A 2 ) n (O.A 3 ) p [A1] A 1 represents an organic group having 2 to 12 carbon atoms and having at least one structure selected from the group consisting of the formulae [2-a] to [2-e] and the formula [2-i], and A 2 represents a hydrogen atom or an alkyl group having 1 to 5 carbon atoms, A 3 represents an alkyl group having 1 to 5 carbon atoms, m represents an integer of 1 or 2, n represents an integer of 0 to 2, and p represents an integer of 0 to 3, wherein m+n+p is 4, (B 1 ) n Si(OB 2 ) 4-n [A2] B 1 represents a hydrogen atom or an alkyl group having 1 to 5 carbon atoms, B 2 represents an alkyl group having 1 to 5 carbon atoms, and n represents an integer of 0 to 3.

10. The liquid crystal alignment agent according to claim 9, wherein The alkoxysilane of formula [A1] is at least one selected from allyltriethoxysilane, allyltrimethoxysilane, diethoxymethylvinylsilane, dimethoxymethylvinylsilane, triethoxyvinylsilane, vinyltrimethoxysilane, vinyltri(2-methoxyethoxy)silane, 3-(triethoxysilyl)propylmethacrylate, 3-(trimethoxysilyl)propylacrylate, and 3-(trimethoxysilyl)propylmethacrylate, The alkoxysilane of the formula [A2] is at least one selected from tetramethoxysilane, tetraethoxysilane, tetrapropoxysilane, and tetrabutoxysilane.

11. The liquid crystal aligning agent according to claim 1 or 2, wherein The liquid crystal alignment agent further includes a crosslinking compound, and the crosslinking compound has at least one selected from an epoxy group, an isocyanate group, an oxetane group, a cyclocarbonate group, a hydroxyl group, a hydroxyalkyl group, and a lower alkoxyalkyl group.

12. The liquid crystal aligning agent according to claim 1 or 2, wherein The compound of the formula [1] is used in a proportion of 0.01 to 20 parts by mass relative to 100 parts by mass of all polymers in the liquid-crystal aligning agent.

13. The liquid crystal aligning agent according to claim 1 or 2, wherein The polymer has a repeating unit having at least one structure selected from the group consisting of the formulae [2-a] to [2-e] and the formula [2-i], wherein the repeating unit is contained in an amount of 10 to 70 mol % based on all repeating units constituting the polymer. 14 . A liquid crystal aligning film obtained from the treating agent for liquid crystal aligning according to claim 1 . 15 . A liquid crystal display element comprising the liquid crystal alignment film according to claim 14 .